Multiple CPA−laser points and anisotropic reflection resonances in PT−symmetric Rudin-Shapiro photonic multilayers. (August 2022) - Wu, Min; Zhong, Dong; Zhao, Dong; Liu, Fangmei; Fang, Ming; Shen, Jing
Abstract: We theoretically explore the CPA−LPs (coherent-perfect-absorber−laser points) directional dependence of reflected light waves at the in quasi-periodicity photonic multilayers. Two dielectric slabs with different refractive indices arrange alternately to form the Rudin-Shapiro (RS) photonic multilayers and the whole system satisfies parity-time (PT) symmetry simultaneously. The PT−symmetric RS structures support optical fractal resonant states and can also localize the electric field of transmission modes greatly. The optical fractal resonances may incorporate and CPA−LPs are induced by modulating the light frequency and the gain/loss factor of materials. The complex phase of reflection coefficient and the electric filed distribution are anisotropic for the left and right incident light waves. The anisotropy is especially remarkable near the CPA−LPs. The CPA−LPs could be regulated by the incident angle and the LPs quantity increases with the increase of the generation number of RS sequence as well. This study has potential applications of optical amplifiers and lasers. Graphical Abstract: ga1